2019
DOI: 10.1530/ec-19-0225
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of CYP17A1 and CYP1B1 polymorphisms in male breast cancer risk

Abstract: Breast cancer in men is a rare and still poorly characterized disease. Inherited mutations in BRCA1, BRCA2 and PALB2 genes, as well as common polymorphisms, play a role in male breast cancer genetic predisposition. Male breast cancer is considered a hormone-dependent tumor specifically related to hyperestrogenism. Polymorphisms in genes involved in estrogen biosynthesis and metabolism pathways, such as CYP17A1 and CYP1B1, have been associated with breast cancer risk. Here, we aimed to investigate the role of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…Another Italian study suggested that SULT1A1 p.Arg213His polymorphism (rs9282861) would act as a low-penetrance risk allele for MBC and would be associate with HER2 overexpression in tumors [ 133 ]. A polymorphism in the CYP17 gene leading to increased serum levels of estrogen was initially suggested to be implicated in the development of MBC [ 134 ], but a larger recent study ruled out that possibility [ 135 ].…”
Section: Inherited Pathogenic Variants Contribution To Mbc Developmentmentioning
confidence: 99%
“…Another Italian study suggested that SULT1A1 p.Arg213His polymorphism (rs9282861) would act as a low-penetrance risk allele for MBC and would be associate with HER2 overexpression in tumors [ 133 ]. A polymorphism in the CYP17 gene leading to increased serum levels of estrogen was initially suggested to be implicated in the development of MBC [ 134 ], but a larger recent study ruled out that possibility [ 135 ].…”
Section: Inherited Pathogenic Variants Contribution To Mbc Developmentmentioning
confidence: 99%
“…Rizzolo et al in their study assessing 597 male breast cancers with 1022 controls found out that CYP17A1 and CYP1B1 polymorphisms do not contribute significant risk of male breast cancer [12].…”
Section: Geneticsmentioning
confidence: 96%
“…A few studies addressed the role of low-penetrance variants in MBC susceptibility through GWAS or a candidate SNP genotyping approach [41,42,44,[156][157][158][159][160][161]. Overall, five loci were associated with increased MBC risk.…”
Section: Common Low-penetrance Risk Variantsmentioning
confidence: 99%